Evaluation of Blood Loss and Implant Alignment after Total Knee Arthroplasty with Inertial Based Extramedullary Femoral Cutting Guide - Bonanzinga, Tommaso; Tanzi, Piergiuseppe; Pia Neri, Maria; Iacono, Francesco; Mazzola, Claudio; Belluati, Alberto; Colombelli, Andrea; Zaffagnini, Stefano; Marcacci, Maurilio (Joints, 2018)
Purpose The purpose of this study was to compare, in terms of blood loss and implant alignment, a new generation of smart extramedullary (EM) cutting guides with the conventional intramedullary (IM) guide for total knee arthroplasty (TKA). The hypothesis was that the EM system would result in less blood loss and fewer days of hospitalization, while ensuring equal or higher accuracy in the alignment of the femoral implant.Methods Thirty-six patients were enrolled for the present study: 18 patients underwent TKA using the EM guide and for the other 18 patients the IM guide was used. Preoperative and postoperative X-rays were acquired. The preoperative and postoperative hemoglobin values were compared. Lastly, length of hospital stay was recorded.Results The hemoglobin difference was significantly lower in the EM group. The alignment of the prosthetic femoral implant in the two groups was comparable but all patients in the EM cohort had a final alignment within 3 degrees of range on the frontal view, while 22% of the patients in the IM cohort had a final alignment exceeding 3 degrees of range. The mean hospitalization duration showed no significant difference between groups, though EM group showed 1.6 days less compared with IM group.Conclusions The inertial-based EM guide system could be useful for decreasing blood loss compared with conventional guide. This device tended to have better results even in terms of accuracy, but this difference was not significant.Level of Evidence This is a level II, prospective cohort study.
Keywords: total knee arthroplasty; extramedullary guide; blood loss; alignment; cutting guides